CD81 interacting proteins - Martins, Soraia Alexandra Araújo (2018)
Fertilization is a multistep and complex process culminating in the merge of gamete membranes, cytoplasmic unity and fusion of genome. CD81 is a tetraspanin protein that participates in sperm-oocyte interaction, being present at the oocyte surface. CD81 has also been implicated in other biological processes, however its specific function and molecular mechanisms of action remain to be elucidated. The interaction between CD81 and its binding partner proteins may underlie the CD81 involvement in a variety of cellular processes and modulate CD81/interactors specific functions. Interestingly, in a Yeast two Hybrid system previously performed in our lab, CD81 has emerged as a putative interactor of the Amyloid Precursor Protein (APP). In the work here described, bioinformatics analyses of CD81 interacting proteins were performed and the retrieved information used to construct a protein-protein interaction network, as well as to perform Gene Ontology enrichment analyses. CD81 expression was further evaluated in CHO, GC-1 and SH-SY5Y cell lines, and in human sperm cells. Additionally, its subcellular localization was analyzed in sperm cells and in the neuronal-like SH-SY5Y cell line. Subsequently, coimmunoprecipitation assays were performed in CHO and SH-SY5Y cells to attempt to prove the physical interaction between CD81 and APP. A functional interaction between these two proteins was accessed thought the analyses of the effects of CD81 overexpression on APP levels. A co-localization analysis of CD81 and some interactors proteins retrieved from the bioinformatics analyses, such as APP, AKT1 and cytoskeleton-related proteins, was also performed in sperm cells and in SH-SY5Y cells. The effects of CD81 in cytoskeleton remodeling was evaluated in SH-SY5Y cells through monitoring the effects of CD81 overexpression in actin and tubulin levels, and analyzing the colocalization between overexpressed CD81 and F-actin. Our results showed that CD81 is expressed in all cell lines tested, and also provided the first evidence of the presence of CD81 in human sperm cells. CD81 immunoreactivity was predominantly detected in the sperm head, including the acrosome membrane, and in the midpiece, where it co-localized with APP, as well as in the post-acrosomal region. Furthermore, CD81 co-localizes with APP in the plasma membrane and in cellular projections in SH-SY5Y cells, where CD81 overexpression has an influence on APP levels, also visible in CHO cells. The analysis of CD81 interacting proteins such as AKT1 and cytoskeletonrelated proteins showed that CD81 is involved in a variety of pathways that may underlie cytoskeleton remodeling events, related to processes such as sperm motility, cell migration and neuritogenesis. These results deepen our understanding on the functions of CD81 and some of its interactors in sperm and neuronal cells.